Huckleberry, Garden—Solanum melanocerasium All - James M. Stephens (EDIS, 2003)
This document provides an overview of the garden huckleberry (Solanum melanocerasium), an edible plant related to the common nightshade. It describes the plant’s appearance, cultivation methods, and uses, noting its resemblance to a pepper bush and its production of small, black berries. While often confused with poisonous nightshades, the garden huckleberry is considered safe and is used in preserves and cooked dishes. The plant grows well in warm climates like Florida and requires similar care to pepper plants, with minimal pest issues observed in trials. Original publication date May 1994.